English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

use addition method

2007-03-14 02:31:55 · 7 answers · asked by Anonymous in Science & Mathematics Mathematics

7 answers

I) |3x + 2y -3z=8
II) |-2x + 3y + 2z=10
III) |x + y - z=2

Addition:
II) |-2x + 3y + 2z=10
III) |2x + 2y - 2z=4 (2)
----------------------------
-2x + 2x + 3y +2y + 2z - 2z = 14
5y = 14
y = 14/5 = 2.8

III) |x + y - z=2
y = 2 + z - x
2.8 - 2 = z - x
z - x = 0.8
-x = 0.8 - z
x = -0.8 + z

x + y -z = 2
-0.8 + 2.8 - z = 2
2 - z = 2
-z = 2-2
So, z = 0

Answer:
x = -0.8
y = 2.8
z = 0
::==::

2007-03-14 03:13:39 · answer #1 · answered by aeiou 7 · 0 0

seventy seven. x - 3y + z = 6 3x + y - z = -2 2x + 2y - z = a million enable's p.c.. out the 1st 2 equations: x - 3y + z = 6 3x + y - z = -2 upload those at the same time and get: 4x - 2y = 4 enable's look on the final 2 equations: 3x + y - z = -2 2x + 2y - z = a million ---> -2x - 2y + z = -a million upload those at the same time and get: x - y = -3 placed the previous 2-variable equations at the same time: 4x - 2y = 4 x - y = -3 ----> -2x + 2y = 6 including those at the same time we get: 2x = 10 x = 5 Use one in all the two-variable equation to locate y: 5 - y = -3 y = 5 + 3 = 8 Use between the unique equations to locate z: z = 2(5) + 2(8) - a million = 25 106. 3x +2y - 3z = 8 2x + 3y + 2z = 10 x + y - z = 2 enable's look on the 1st 2 equations: 3x + 2y - 3z = 8 -----> 6x + 4y - 6z = sixteen 2x + 3y + 2z = 10 --> 6x + 9y + 6z = 30 including those 2 at the same time we get: 12x + 13y = 40 six enable's look on the final 2 equations: 2x + 3y + 2z = 10 x + y - z = 2 ---------> 2x + 2y - 2z = 4 including those at the same time we get: 4x + 5y = 14 placed the previous 2-variable equations at the same time: 12x + 13y = 40 six 4x + 5y = 14 -----> -12x - 15y = -40 two including those at the same time we get: -2y = 4 y = -2 Use one in all the two-variable equation to locate x: 4x + 5(-2) = 14 4x = 24 x = 6 Use between the unique equations to locate z: 6 - 2 - z = 2 z = 6 - 2 -2 = 2 i choose to bury my face on your boobs. :)

2016-12-18 13:23:47 · answer #2 · answered by ? 4 · 0 0

42.

"The Answer to Life, The Universe and Everything"........Deepthought

2007-03-14 02:34:35 · answer #3 · answered by PrincessPlum 4 · 0 0

2x+6y-2z=20?

2007-03-14 02:35:22 · answer #4 · answered by steven c 2 · 0 0

no solution. the denominator matrix is a zero matrix

2007-03-14 02:38:45 · answer #5 · answered by George Atento 2 · 0 0

Why the hell would i care

2007-03-14 02:34:31 · answer #6 · answered by Bertie D 4 · 0 0

maybe 5x+4z=-6?

2007-03-14 02:48:51 · answer #7 · answered by ziggyzp77 2 · 0 0

fedest.com, questions and answers